Implementasi Julian Day dalam Penentuan Waktu Shalat - sutono sutono (Komputika : Jurnal Sistem Komputer, 2017)
The purpose of designing Prayer Hours is to overcome the problems of prayer times every day, starting from Shubuh to Isha '. By using the algorithm for calculating the prayer time scheduling formula based on time zone, longitude, latitude, altitude, date, month and year, we do not need to create a database and include it in Arduino memory, making it easier to use prayer time calculations without updating data annually.